2018
DOI: 10.5398/tasj.2018.41.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Intestinal Profiles of Tegal Duck Fed Ration Supplemented with Prebiotics.

Abstract: This research was aimed to determine the effects of prebiotics on performance and gastrointestinal profiles of Tegal ducks. One hundred two-month-old male Tegal ducks were distributed into 5 treatment groups; R 0 = control; R 1 = FOS; R 2 = MOS; R 3 = Inulin; and R 4 = natural prebiotic (water hyacinth/Eichhornia crassipes). The prebiotics were given at 0.2% of the total feed (w/w). The observed variables were performances and gastrointestinal profiles. This study used a completely randomized design and contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 13 publications
1
14
1
2
Order By: Relevance
“…The findings of Cengiz et al 2012could support these results and Koksal et al (2013) who reported that MOS and βglucans prebiotic insertion had no beneficial effect on growth rate and feed consumption in broiler chickens exposed to post-hatch holding time stress. Also, Iriyanti et al (2018) reported that performance (live weight, body weight gain, and feed intake) of ducks were not significantly affected by Mannanoligosaccharide supplementation at 0.2% of the total feed. These findings disagree with previous works done by Sohail et al (2012) which revealed that dietary supplementation of MOS enhanced growth and decreased corticosterone concentrations in heat stressed broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of Cengiz et al 2012could support these results and Koksal et al (2013) who reported that MOS and βglucans prebiotic insertion had no beneficial effect on growth rate and feed consumption in broiler chickens exposed to post-hatch holding time stress. Also, Iriyanti et al (2018) reported that performance (live weight, body weight gain, and feed intake) of ducks were not significantly affected by Mannanoligosaccharide supplementation at 0.2% of the total feed. These findings disagree with previous works done by Sohail et al (2012) which revealed that dietary supplementation of MOS enhanced growth and decreased corticosterone concentrations in heat stressed broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Rahman et al (2017) showed that supplementation of onion (Allium cepa L.) extract/powder modified the gut microbiota, increased villus health, increased nutrient digestibility and absorption. Iriyanti et al (2018) also reported that the small intestine functions as feed digestion and nutrients absorptions that were influenced by the epithelial intestine and the conditions and amount of microvilli.…”
Section: Morphology Of Jejunal Intestinementioning
confidence: 99%
“…Therefore, the exploration of alternative substances for replacing AGPs has been extensively elucidated. Previous studies indicated that organic acids (Salah et al, 2019), phytobiotics (Ripon et al, 2019), prebiotics (Iriyanti et al, 2018), and probiotics (Sofyan et al, 2019) have potencies for replacing AGPs.…”
Section: Introductionmentioning
confidence: 99%